The Challenges in Business Process Improvement Training Transfer: An Inductive Exploration from the Australian Context - Thennakoon, D.; Bandara, W.; French, E. (My University, 2016)
This paper is about the issues in Business Process Improvement (BPI) training transfer. There is ongoing training provided for BPIs. However, industry reports and research shows that the number of implementation failures in BPI have been substantial and the problem still remains unsolved. This paper places special emphasis on the transfer of BPI training. An exploratory and inductive approach was taken where the findings indicate various issues around eight main themes, the main being that of resistance. Our research 1) unearths the issues around BPI training transfer; 2) informs BPI training literature on the importance of understanding the issues around BPI training transfer and; 3) informs the practice on ways of overcoming the issues related to BPI training transfer.
Keywords: Training transfer; Business Process Improvement; Resistance